2009
DOI: 10.1002/jso.21291
|View full text |Cite
|
Sign up to set email alerts
|

Promoter hypermethylation of tumor‐related genes in peritoneal lavage and the prognosis of patients with colorectal cancer

Abstract: These findings suggest that disseminated tumor cells in PLF detected by QMSP may correlate with the postoperative clinical course of patients undergoing curative surgery for CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 31 publications
3
11
1
Order By: Relevance
“…The relation of p16 methylation with clin-114 icopathological variables, in these patients, has yield discrepancies in the literature. Although methylation could not be associated to clinicopathological variables by some authors (28,38), it has been associated to the following: Dukes stage and lymphatic invasion (35); also to age, sex, tumor location, differentiation grade and histological type (36). In this study, the p16 gene promoter methylation was found to be associated with both, poor differentiation grade and proximal tumor location.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…The relation of p16 methylation with clin-114 icopathological variables, in these patients, has yield discrepancies in the literature. Although methylation could not be associated to clinicopathological variables by some authors (28,38), it has been associated to the following: Dukes stage and lymphatic invasion (35); also to age, sex, tumor location, differentiation grade and histological type (36). In this study, the p16 gene promoter methylation was found to be associated with both, poor differentiation grade and proximal tumor location.…”
Section: Discussioncontrasting
confidence: 61%
“…None of the previously published studies of p16 showed high population size, with so extended follow-up in homogeneous population, only with sporadic cases with no previous treatment (24)(25)(26)(27)(28)(29). The only cases who reported higher population size with survival analyses in long follow-up whether had lower median follow up (23) whether consisted of multicenter studies, introducing variability through diverse laboratory analyses and different clinical management, including family history cases (25).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that the frequencies of aberrant promoter methylation were 16% for cadherin 1, 2% for p16, 4% for MGMT and 24% for APC (47). An aberrant methylation of ≥1 of these genes was identified in 45 of 51 (88%) primary tumors (48). In the present cohort, APC was methylated in 33% of patients with early oCRC and in 53.7% of patients with mCRC.…”
Section: Discussionsupporting
confidence: 53%
“…Hypermethylation of the APC promoter has been reported in early steps of carcinogenesis in several tumors (46). A previous study reported that the frequencies of aberrant promoter methylation were 16% for cadherin 1, 2% for p16, 4% for MGMT and 24% for APC (47). An aberrant methylation of ≥1 of these genes was identified in 45 of 51 (88%) primary tumors (48).…”
Section: Discussionmentioning
confidence: 92%
“…37,40,[43][44][45][46][47][48][49] The methylation of p16, as evaluated in DNA extracted from primary tumors, peritoneal lavage fluid, and serum from patients with colorectal cancer, has been related to more advanced tumor stage and to significantly poorer overall and disease-free survival rates. 37,45,50,51 It is noteworthy that protein expression of p16 is correlated inversely with the degree of methylation, supporting the argument that immunohistochemistry for the protein could be used as a surrogate marker for p16 epigenetic silencing. 47 Furthermore, the use of p16 protein expression has been suggested as a screening tool for the selection of patients who undergo genetic testing for Lynch syndrome.…”
Section: Original Article 4480mentioning
confidence: 55%